Psychometric Properties of the Persian Version of Palliative Care Outcome Scale (POS) in Adult Patients With Cancer - Sirati Nir, Masoud; Rassouli, Maryam; Ebadi, Abbas; Moosavi, Soolmaz; Pakseresht, Maryam; Hasan Shiri, Fatemeh; Souri, Hossein; Nasiri, Morteza; Karami, Maryam; Fereidouni, Armin; Barasteh, Salman (Frontiers in Psychology, 2022)
Background: Measuring the outcomes of palliative care plays an important role to improve the quality, efficiency and availability of these services in cancer patients. Using valid, reliable and culturally appropriate tools has a considerable role to measure these outcomes. This study aimed to assess the psychometric properties of translated version of the palliative outcome scale. Methods: This methodological study was conducted in two outpatient clinics related to Shohada Tajrish and Baqiyatallah hospitals in Tehran in 2019-2020. The translation was done using the Forward-Backward approach after gaining permission from the developer. Face validity was tested with 10 cancer patients through cognitive interviewing, as well as content validity with four experts. Construct validity was performed by (n=203) exploratory factor analysis and confirmation (N = 150). To assess the reliability, internal consistency was assessed by using Cronbach’s Alpha Coefficient, and relative stability was assessed using interclass correlation coefficient (ICC). Furthermore, interpretability and ceiling and floor effects were assessed. Results: A total of 353 cancer patients under the palliative care were included in the study. Three psychological (30.00%), physical (12.25%), and social factors (12.08%) with a cumulative variance of 54.34% were extracted in exploratory factor analysis. Confirmatory factor analysis showed that the model has a good fit of information. Cronbach’s Alpha Coefficient for scale was 0.719. Furthermore, the ICC was 0.812. The scale was interpretable and ceiling and floor effects were 0 %. Conclusion: Persian version of the palliative Outcome Scale was evaluated as a valid and reliable tool; therefore, it can be used by the clinician to monitor the consequences of palliative care in Iranian cancer patients.